CARDIORESPIRATORY MONITORING OF CHILDREN AND ADOLESCENTS WITH METABOLIC SYNDROME AGED 10-17 YEARS: A CROSS-SECTIONAL DESCRIPTIVE STUDY - Aliusef, Maiia; Churylina, Alina; Mitiuriaeva, Inga; Gnyloskurenko, Ganna (Eastern Ukrainian Medical Journal, 2023)
Study objectives. This study aims to investigate potential differences in sleep parameters between children with metabolic syndrome (MetS) and their healthy counterparts using the portable cardiorespiratory monitoring device SOMNOcheck micro CARDIO.Methods. The study included 71 children and adolescents aged 10 to 17 years, with 39 in the MetS group and 32 in the control group. The main anthropometric parameters were: neck circumference (NC), waist circumference (WC) and waist-to-height ratio (WHtR). All children were assessed using the Friedman tongue position (FTP) scale. Children completed the Epworth Sleepiness Scale for Children and Adolescents (ESS-CHAD) and the Montreal Cognitive Assessment (MoCA). Salivary cortisol was collected in the morning immediately after waking up. The sleep study was performed using a portable SOMNOcheck micro CARDIO device with a special cardiaс sensor. Statistical analysis of the data was performed using EZR version 1.61.Results. Significant differences in cardiorespiratory sleep monitoring were observed between between the MetS and non-MetS groups. Patients with MetS had higher daytime sleepiness scores and lower MoCA scores compared to the control group. Cortisol levels in morning saliva showed a marked increase among children with obstructive apnea/hypopnea index ≥ 1. A logistic regression model established a link between FTP stages III and IV and the autonomous arousal index.Conclusions. These findings highlight the differences (p < 0.05) in sleep-related parameters between the MetS and non-MetS groups, which may indicate an increased risk of sleep-disordered breathing and cognitive impairment in such children.